Study guides

☆☆

Q: What is 2a x a?

Write your answer...

Submit

Still have questions?

Related questions

The answer is 4a^2.

x + 2a

2a x 3b = 6ab

Since you cannot multiply x by a, in the answer you get ax. 2a * 3x = 6ax

-b/2a. i think.To show this, consider this equation:y = ax² + bx + cFactor out the a:y = a(x² + bx/a + c/a)Then, complete the squares to get:y = a(x² + bx/a + (b/(2a))² + c/a - (b/(2a))²)= a((x + (b/2a))² + c/a - (b/(2a))²)= a(x + (b/2a))² + c - b/(4a)By the vertex form:y = a(x - h)² + k where x = h is the axis of symmetry.So the general axis of symmetry for the quadratic equation is x = -b/(2a).

6 - a²

2a - a = a

We have the algebraic expression: 8a2 - 2aIn order to factorize it, we can just simply pull out 2a and we are now left with this: 2a(4a-1)But, why 2a?In the given algebraic expression we have two terms: 8a2 and -2aNow, we have to look for the common factor of 8a2 and -2a.8a2 = 8 x a x a = 2 x 2 x 2 x a x a-2a = -2 x aCommon factor is 2a. (2 is also the common factor but we need greatest common factor which is 2a)4a - 1 can not be further factorized so the final answer is 2a(4a-1).Visit the link provided below to learn more about factoring.

x2=(4a)(a) x=√4a2 x=2a The geometric mean of a and 4a is 2a

52 times 2a = 104a

The height of an equilateral triangle is √3/2 x side_length. So for an equilateral triangle of side length 2a, the area is: area = 1/2 x base x height 1/2 x (2a) x (√3/2 x 2a) = √3 a2

20 = 1Consider what is the value of 2a ÷ 2a? Any number divided by itself is 1. Thus:2a ÷ 2a = 1The law of indices says that when dividing, they are subtracted, for example:25 ÷ 22 = (2 x 2 x 2 x 2 x 2) ÷ (2 x 2) = 2 x 2 x 2 = 23 = 25-2So 2a ÷ 2a is (also):2a ÷ 2a = 2a-a = 20Since any number subtracted from itself is 0 (= a - a). This must have the same value as before, thus:20 = 1The 2 above can be replaced by any number x which means that any number to the power 0 is 1:x0 = 1

4a

6

The answer is 2a because of the two a's equal 2a

if f(x) = 3x - 10, then whatever is put (substituted) for x in the "f(x)" bit is substituted for x in the "3x - 10" bit. Thus f(2a) = 3(2a) - 10 = 6a - 10.

4a

8a2b

Urmm 4ab ?

144a2b

3a x 2a =24

x=-b/2a [negative B over 2A]

7

General form is a quadratic equation in the form f(x) = ax2 + bx + c. To change this form into the standard form: * Given function f(x) f(x) = ax2 + bx + c * Factor coefficient a out of the terms in x2 and x f(x) = a[ x2 + (b/a)x ] + c * Add and subtract (b/2a)2 inside the parentheses f(x) = a[ x2 + (b/a)x + (b/2a)2 - (b/2a)2 ] + c * Note that x2 + (b/a)x + (b/2a)2 * Can be written as [x + (b/2a)]2 * We now write f as follows f(x) = a[ x + (b/2a) ]2 - a(b/2a)2 + c * Which can be written as f(x) = a[ x + (b/2a) ]2 - (b2/4a) + c * Also found (word for word) on http://www.analyzemath.com/quadraticg/quadraticg.htm

The quadratic formula originated from the concept of completing the square. let's take ax2 + bx + c = 0. To complete the square, solve for x. Subtract c. ax2 + bx = -c. Then divide by a [notice- if there is no a value, then a=1]. x2 + bx/a = -c/a. Add (b/2a)2 to both sides. x2 + bx/a + b2/4a2 = -c/a + b2/4a2 Factor/Reformat. (x + b/2a)2 = (b2-4ac) / 4a2 (x + b/2a)2 = [(b2-4ac) / 2a]2 Square-root both sides. x + b/2a = ± √(b2-4ac) / 2a Subtract b/2a. x = -b/2a ± √(b2-4ac) / 2a Combine terms. x = [-b ± √(b2-4ac)] / 2a

People also asked